2017
DOI: 10.1111/jpc.13728
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of developmental concern amongst infants at 12 months following hospitalised parechovirus infection

Abstract: A high proportion of infants show developmental concern at 12-month follow-up post-hospitalisation with HPeV infection. Clinical features during hospitalisation were not associated with adverse outcomes at 12 months. These results suggest that careful follow-up of young infants hospitalised with HPeV disease may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…This 2‐yearly pattern is similar to that observed in the United Kingdom 13 . However, in contrast to other countries, epidemics in Australia have been larger and associated with more severe disease (and poorer clinical outcomes) 14 , 15 . Recently, whole genome sequencing has shown that the first Australian epidemic was likely caused by a novel recombinant HPeV3 16 …”
Section: Virology and Epidemiologysupporting
confidence: 70%
See 1 more Smart Citation
“…This 2‐yearly pattern is similar to that observed in the United Kingdom 13 . However, in contrast to other countries, epidemics in Australia have been larger and associated with more severe disease (and poorer clinical outcomes) 14 , 15 . Recently, whole genome sequencing has shown that the first Australian epidemic was likely caused by a novel recombinant HPeV3 16 …”
Section: Virology and Epidemiologysupporting
confidence: 70%
“…Follow‐up studies have shown adverse neurological outcomes in patients with meningoencephalitis, and developmental concern among patients with sepsis‐like illness from the 2013–2014 epidemic 14 , 15 , 23 . A study of Australian infants hospitalised with HPeV3 in 2013 found that 19% showed significant concern in developmental attainment 12–16 months after infection and an additional 50% had some concern based on standardised tools 15 . An earlier study documented severe neurodevelopmental sequelae, including cerebral palsy, central visual impairment and gross motor impairment 14 .…”
Section: Managing Parechovirus Infectionmentioning
confidence: 99%
“…The largest of the four studies to investigate outcomes following HPeV meningitis showed neurodevelopmental sequelae in 14% of infants . Interestingly, findings from the Queensland study are consistent with other long‐term studies of infants with HPeV encephalitis in New South Wales, which show poor long‐term outcomes following hospital discharge . It is not clear whether more pathogenic strains of HPeV circulated during the outbreak in New South Wales compared with circulating strains in Western Europe or whether variation in maternal immunity, age of developing infection or differences in host response to the virus could account for worse outcomes in Australian cases compared with those described in the United Kingdom and Holland.…”
Section: Discussionmentioning
confidence: 52%
“…18 Interestingly, findings from the Queensland study are consistent with other long-term studies of infants with HPeV encephalitis in New South Wales, which show poor long-term outcomes following hospital discharge. 29 Conclusions from this systematic review should be taken with caution due to several limitations. The review only identified 14 studies over the last three decades, which reported outcomes following viral meningitis.…”
Section: Discussionmentioning
confidence: 98%
“…7 Central nervous system conditions such as acute flaccid paralysis, meningitis and encephalitis are more often associated with PeV-3. [10][11][12][13] Inference about differential clinical manifestations is limited for most of the other PeV-A genotypes as they have only been isolated from a few cases.…”
Section: Introductionmentioning
confidence: 99%